Hierarchical three-dimensional MnO2/carbon@TiO2 nanotube arrays for high-performance supercapacitors. Issue 68 (5th July 2016) - Wang, Zicheng; Wang, Yan; Shu, Xia; Yu, Cuiping; Zhang, Jianfang; Cui, Jiewu; Qin, Yongqiang; Zheng, Hongmei; Zhang, Yong; Wu, Yucheng
Abstract : Highly ordered TiO2 nanotube arrays (TNAs) modified by other materials with enhanced conductivity and capacitance have been considered to be promising anode materials for supercapacitors. Abstract : Highly ordered TiO2 nanotube arrays (TNAs) modified by other materials with enhanced conductivity and capacitance have been considered to be promising anode materials for supercapacitors. In this work, carbon@TiO2 nanotube arrays (CTNAs) were firstly synthesized through a calcination process under an Ar atmosphere. Then the hierarchical three-dimensional MnO2 /carbon@TiO2 nanotube arrays (CMTNAs) were further developed via hydrothermal deposition of uniformly dispersed MnO2 nanoparticles with the help of the in situ reduction effect of the as-obtained carbon layers. The CTNA electrode exhibited a high area capacitance of 5.58 mF cm −2 at a scan rate of 100 mV s −1, which is about 11 times higher than that of the TiO2 nanotube arrays annealed under an air atmosphere (ATNAs). The highest gravimetric capacitance 521.4 A g −1 was achieved with the CMTNAs at a current density of 2 A g −1, and 88.6% of the initial capacitance could be maintained at a current density of 5 A g −1 up to 2000 cycles via a galvanostatic charge–discharge test.